ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diana, Diana; Harahap, Baru (LPPM Universitas Putera Batam, 2020)
This research aims to determine the potential of bankruptcy by using Altman Z-Score model in textile and garment company listed on Indonesia Stock Exchange period 2015- 2019. In this study used a quantitative descriptive approach. This research uses the Purposive sampling method by assigning certain criteria in selecting research samples so that 6 companies are made samples. The data collection techniques used are the documentation and the analytical techniques used are models of the Altman Z-Score modifications. The equation of the Altman Z-Score model is Z